Giardia duodenalis Infection and Pachymeningitis in a Patient With Agammaglobulinemia - Gamze Sonmez; Cigdem Kaya; Merve Erdem; Rahsan Gocmen; Ilhan Tezcan; Deniz Cagdas (Clinical Pediatrics, 2026)
X-linked agammaglobulinemia (XLA) is a rare immunodeficiency caused by a mutation in Bruton’s tyrosine kinase, resulting in profoundly low immunoglobulin levels and susceptibility to recurrent infections. We report a 14-year-old patient with XLA who presented with persistent fever, bloody diarrhea, and headache suggestive of pachymeningitis. The patient had chronic giardiasis. His clinical condition deteriorated with worsening thrombocytopenia, hepatitis, and minimal diffuse dural thickening on brain magnetic resonance imaging, interpreted as pachymeningitis. Empirical immunosuppressive therapy was initiated, but the patient ultimately succumbed to illness. Although Giardia has been linked to various extra-intestinal manifestations, its association with meningitis or pachymeningitis is not reported. This case highlights the complexity of managing immunocompromised patients with unexplained fever and neurological symptoms, emphasizing the need for further research into the potential neurological effects of Giardia infection.